Le elezioni comunali di Parma (2012-2017): l'effetto Pizzarotti - Mara Morini (QOE-IJES)
The article describes the political evolution of the Italian Five Star Movement (Movimento 5 Stelle - M5S) at the local level (2009-2012) with a specific reference to the «Italian Stalingrad» i.e. the city of Parma. In the administrative elections held in 2012 the M5S was able to get its first Major, Federico Pizzarotti, who was unexpectedly elected in the second round defeating the center left coalition. Born as a local and civic experience in the so called Meetup (local party meetings), the M5S of Parma is an example of «overpromising populism» (Mény & Surel 2000) accused by Beppe Grillo (the central office) of a compromise-collusion made by Pizzarotti with the «old» power (traditional parties). Firstly, a short overview of the local evolution of M5S is given in order to better understand its level of local penetration and representation between 2009-2014. Secondly, the analysis of the 2012-2017 electoral campaigns will be described taken into consideration the political characteristics of all the competitors and the main determinants of Pizzarotti's two electoral success. Thirdly, some hypothesesabout the future of the «Effetto Parma» civic party and Pizzarotti's leadership at the local and national level will be provided.